AS POLÍTICAS PÚBLICAS NA PERSPECTIVA DA DESIGUALDADE NO NOROESTE COLONIAL GAÚCHO - FILHO, CARLOS J. M.; WESENDONCK, CLÁUDIA; SIEDENBERG, DIETER R.; TENORIO, FERNANDO G.; DALLEPIANE, SABRINA; ALLEBRANDT, SERGIO L. (Salão do Conhecimento, 2013)
Resumo